Fungsi WHO Dalam Penanganan Pandemi Covid-19 dan Dampaknya Bagi Hak Asasi Manusia - Janri Jacob Bakarbessy (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The World Health Organization (WHO) is one of the United Nations agencies that acts as the international public health coordinator. The function of the World Health Organization (WHO) is to achieve maximum health for all people around the world. But in reality, WHO seems powerless to handle the Covid-19 pandemic and provide protection for human rights.Purposes of the Research: The purpose of this study is to see and study the implementation of WHO's function in mitigating the Covid-19 pandemic and its impact on human rights.Methods of the Research: The research method in this writing uses the type of research